Wybrane aspekty polsko-ukraińskiej współpracy gospodarczej po roku 1990 - Stermach, Patrycja (Selected Aspects of Economic Co-operation between Ukraine and Poland after 1990, 2008)
Shortly after independence was ratified in December 1991, the Ukrainian Government liberalized most prices and erected a legal framework for privatization, but widespread resistance to reform within the government and the legislature soon stalled reform efforts and led to some backtracking. Output by 1999 had fallen to less than 40% of the 1991 level. Loose monetary policies pushed inflation to hyperinflationary levels in late 1993. Ukrainian Government officials eliminated most tax and customs privileges in a March 2005 budget law, bringing more economic activity out of Ukraine's large shadow economy, but more improvements are needed, including fighting corruption, developing capital markets, and improving the legislative framework for businesses. Reforms in the more politically sensitive areas of structural reform and land privatization are still lagging. Outside institutions -particularly the IMF - have encouraged Ukraine to quicken the pace and scope of reforms. In its efforts to accede to the World Trade Organization (WTO), Ukraine passed more than 20 laws in 2006 to bring its trading regime into consistency with WTO standards. GDP growth was 7% in 2006, up from 2.4% in 2005 thanks to rising steel prices worldwide and growing consumption domestically. Although the economy is likely to expand in 2007, long-term growth could be threatened by the government's plans to reinstate tax, trade, and customs privileges and to maintain restrictive grain export quotas. Poland has steadfastly pursued a policy of economic liberalization since 1990 and today stands out as a success story among transition economies. In 2006, GDP grew 5.3%, based on rising private consumption, a 16.7% jump in investment, and burgeoning exports. Consumer price inflation - at 1.3% in 2006 - remains among the lowest in the EU. Since 2004, EU membership and access to EU structural funds have provided a major boost to the economy. Unemployment, which stood at 15% in December 2006, is still the highest in the EU. Ukraine represents less than 1% of total EU trade. Poland is Ukraine's 4th trading partner, Ukraine is 7th Polish trade partner. The EU is Ukraine's largest trading partner accounting for about 32% of Ukraine's total trade. (In 2005 Ukraine's exports to the EU-25 amounted to 7.7 billion euros, and imports 13.0 billion euros).12 In December 2005 the EU granted to Ukraine Market Economy Status, which is in particular relevant for trade defense investigations. The review of the existing feasibility study on establishing a Free Trade Area between Ukraine and the EU will be accelerated with a view to enable an early start of negotiations once Ukraine has joined the World Trade Organization (WTO). Other important areas include the need to improve Ukraine's investment climate, to reduce VAT arrears and to tackle corruption that acts as a significant deterrent for foreign investors.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 12, s. 206-214